2014
DOI: 10.1001/jama.2014.8637
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oximetry on Hospitalization in Bronchiolitis

Abstract: clinicaltrials.gov Identifier: NCT00673946.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
99
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 25 publications
1
99
0
3
Order By: Relevance
“…However, this recommendation has been criticized. 26,27 Additionally, interobserver agreement is an important issue when calculating CSS values for bronchiolitis patients. 28 We found that the BNP level at the time of admission to the ED yielded objective and accurate information on bronchiolitis severity and morbidity in children.…”
Section: Discussionmentioning
confidence: 99%
“…However, this recommendation has been criticized. 26,27 Additionally, interobserver agreement is an important issue when calculating CSS values for bronchiolitis patients. 28 We found that the BNP level at the time of admission to the ED yielded objective and accurate information on bronchiolitis severity and morbidity in children.…”
Section: Discussionmentioning
confidence: 99%
“…30 The previous study suggesting decreased LOS noted lack of a standard oxygen saturation for initiating supplemental oxygen in the earlier study, leading to prolonged LOS 2 ; we use 90% as a cutoff for initiating supplemental oxygen at our center. Although multiple studies have demonstrated that oxygen saturation influences admission rates, 31,32 other factors such as poor oral intake and need for aggressive suctioning may be important drivers of LOS. Studies have described an association between decreased oral intake and nasal suctioning with LOS in infants with bronchiolitis, [33][34][35] and our interventions did not have any impact on suctioning practices or improving oral intake for patients.…”
Section: Discussionmentioning
confidence: 99%
“…A study illustrating this conundrum was recently published. 19 Treatment of 108 infants with symptoms of mild-to-moderate bronchiolitis and a true saturation of 88% or more presenting to an emergency room in a Toronto hospital were studied. Researchers were evaluating the effect that oximetry measurements during pulse oximetry monitoring had on care decisions while patients were being evaluated for treatment and/or hospital admission in the emergency department.…”
Section: Confusion Arises When Monitors Are Used To Make a Diagnosismentioning
confidence: 99%